Republic of Serbia : Request for a 30-Month Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Serbia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
Serbia succeeded in addressing macroeconomic imbalances and restoring confidence and growth under the precautionary SBA which expired in February 2018. Fiscal sustainability has been restored by placing public debt on a firm downward path and the external position has been realigned with fundamentals. Monetary policy has kept inflation under firm control, while supporting economic recovery. The resilience of the financial sector has improved. Progress has also been made on structural and institutional reforms, including in rationalizing the size of public sector employment, addressing fiscal risks from SOEs, and improving the business environment. However, challenges remain for achieving robust, inclusive, and sustainable growth, which Serbia needs for faster income convergence with its EU peers. The authorities requested a 30-month Policy Coordination Instrument (PCI) to provide a framework for continued macroeconomic stability and reforms, and maintain close policy dialogue with staff.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet